Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am working through the derivation of an adiabatic process of an ideal gas $pV^{\gamma}$ and I can't see how to go from one step to the next. Here is my derivation so far which I understand:

$$dE=dQ+dW$$ $$dW=-pdV$$ $$dQ=0$$ $$dE=C_VdT$$



differentiate the ideal gas equation $pV=Nk_BT$


rearrange for $dT$ and substitute into the 1st law:


The next part is what I am stuck with I can't see how the next line works specifically how to go from $\frac{C_V}{C_p-C_V}=\frac{1}{\gamma -1}$

using the fact that $C_p-C_V=Nk_B$ and $\gamma = \frac{C_p}{C_V}$ it can be written

$$\frac{C_v}{Nk_B}=\frac{C_V}{C_p-C_V}=\frac{1}{\gamma -1}$$.

If this could be explained to me, I suspect it is some form of algebraic rearrangement that I am not comfortable with that is hindering me.

share|cite|improve this question
up vote 2 down vote accepted

I think the last line does not follow from the previous steps. It is used to show how $\gamma$ comes in place, so I extrapolated a bit and show the next few steps:

Since $$ \frac{C_V}{Nk_B} = \frac{C_V}{C_p-C_V} = \frac{\frac{C_V}{C_V}}{\frac{C_p}{C_V}-\frac{C_V}{C_V}}=\frac{1}{\gamma-1} $$ Therefore, $$ \frac{C_V}{Nk_B} (pdV+Vdp)= \frac{1}{\gamma-1} (pdV+Vdp) = -pdV $$ Dividing both sides with $pdV$: $$ \frac{1}{\gamma-1}(1+\frac{V}{p}\frac{dp}{dV})=-1 $$ Continue to simplify the expressions and you will reach your result of $pV^\gamma$is constant.

share|cite|improve this answer

Hint: Divide both numerator and denominator by $C_V$: $$\frac{C_V}{C_p-C_V} = \frac{1}{C_p/C_V -1}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.